If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying sin(t + -10x) = cos(10x + -1t) (t * ins + -10x * ins) = cos(10x + -1t) (inst + -10insx) = cos(10x + -1t) Reorder the terms: inst + -10insx = cos(-1t + 10x) inst + -10insx = (-1t * cos + 10x * cos) inst + -10insx = (-1cost + 10cosx) Solving inst + -10insx = -1cost + 10cosx Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Reorder the terms: cost + -10cosx + inst + -10insx = -1cost + 10cosx + cost + -10cosx Reorder the terms: cost + -10cosx + inst + -10insx = -1cost + cost + 10cosx + -10cosx Combine like terms: -1cost + cost = 0 cost + -10cosx + inst + -10insx = 0 + 10cosx + -10cosx cost + -10cosx + inst + -10insx = 10cosx + -10cosx Combine like terms: 10cosx + -10cosx = 0 cost + -10cosx + inst + -10insx = 0 Factor out the Greatest Common Factor (GCF), 's'. s(cot + -10cox + int + -10inx) = 0Subproblem 1
Set the factor 's' equal to zero and attempt to solve: Simplifying s = 0 Solving s = 0 Move all terms containing i to the left, all other terms to the right. Add '-1s' to each side of the equation. s + -1s = 0 + -1s Remove the zero: 0 = -1s Simplifying 0 = -1s The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(cot + -10cox + int + -10inx)' equal to zero and attempt to solve: Simplifying cot + -10cox + int + -10inx = 0 Solving cot + -10cox + int + -10inx = 0 Move all terms containing i to the left, all other terms to the right. Add '-1cot' to each side of the equation. cot + -10cox + int + -1cot + -10inx = 0 + -1cot Reorder the terms: cot + -1cot + -10cox + int + -10inx = 0 + -1cot Combine like terms: cot + -1cot = 0 0 + -10cox + int + -10inx = 0 + -1cot -10cox + int + -10inx = 0 + -1cot Remove the zero: -10cox + int + -10inx = -1cot Add '10cox' to each side of the equation. -10cox + int + 10cox + -10inx = -1cot + 10cox Reorder the terms: -10cox + 10cox + int + -10inx = -1cot + 10cox Combine like terms: -10cox + 10cox = 0 0 + int + -10inx = -1cot + 10cox int + -10inx = -1cot + 10cox The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 4^-3x3^4x4^2/3^5x4^-2 | | 2b-4/2=10 | | 5n^2=9n-2 | | 3c-5c+9= | | 1/64=16^5x-2 | | x=.4x-100 | | (3x-11)+(2x+11)+2y=180 | | 4x^2+8x+18=0 | | -8=2=a/4 | | x^2-16x+52=5 | | x+4-4=5-4 | | x^12-16x+52=5 | | -1/3w+5/8=1/6w+7/8 | | -9+6x=-63 | | f(x)=2*x^2-8*x+3 | | (5.5y+7)3=6.5y-7 | | -5=4y-14 | | 30+2x=-8x | | 16/25:2/5 | | 40/(9-4)*2 | | 9x+24=6z | | F(x)=0.6x+2 | | 5x-14=2.5x+6 | | (3x-22)+80+x=180 | | -16x^2+24x+3=0 | | 5x-x+2x+4x=20 | | .2+3=8.6 | | 17m+3m-5m+3m-12m=18 | | 88+70+x=180 | | 8x-5x=5+14 | | -k+4=9 | | 2/7(d-6)=28 |